Shifting trends of lung tumours and its diagnosis by lung biopsy: a study of 78 cases - Naik, Kinnari S.; Jarag, Mayur; Shah, Pinal; Patel, Mubin; Patel, Amita; Shah, Anand (International Journal of Research in Medical Sciences, 2017)
Background: The objective of the study was to study the spectrum of pathological lesions in patients with lung mass and to study correlation between clinical findings, histopathological pattern and immunohistochemical stains in various biopsy specimen for differentiation and typing of tumors. Methods: This retrospective study was done for the period of three years at Department of Pathology, New Civil Hospital, Surat, India, which is a tertiary health care Centre. Here we studied 78 cases of lung biopsy received in formalin, which were subjected to histopathological examination. Immunohistochemistry was performed as and when required. Results: Total 78 lung biopsy specimens were examined. Out of which, 59 cases (75.6%) were neoplastic, 12 cases(15.4%) were non-neoplastic and 7 cases (9%) were inconclusive. The commonest histological type of malignancy was adenocarcinoma which is associated with peripheral mass lesion, female gender and in non-smokers. Commonest non-neoplastic lesion was tuberculosis. Malignancy was seen quite common in patients presented with lung masses in our institute. Conclusions: Lung tumours are quite common in patients presented with mass lesion. Similar to global trend, adenocarcinoma is the commonest histological type now and associated with change in incidence among women, in non-smokers, molecular alteration and prognosis which need further investigation. Immunohistochemistry is helpful in cases which are not accurately subtyped by histomorphology alone.